2013
DOI: 10.1016/j.yjmcc.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle cells in human atherosclerosis: Proteomic profiling reveals differences in expression of Annexin A1 and mitochondrial proteins in carotid disease

Abstract: Smooth muscle cells (SMC) contribute to the development and stability of atherosclerotic lesions. The molecular mechanisms that mediate their properties are incompletely defined. We employed proteomics and in vitro functional assays to identify the unique characteristics of intimal SMC isolated from human carotid endarterectomy specimens and medial SMC from thoracic aortas and carotids. We verified our findings in the Tampere Vascular Study. Human atheroma-derived SMC exhibit decreased expression of mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…7H-K, HDL inhibited secretion of MCP-1(33.8%, P<0.001), IL-8(37.1%, P<0.001), VCAM-1(37.7%, P<0.001) and E-selectin (41.8%, P<0.001) by TNF-α in HUVECs transfected by empty vector. After transfection of Ad-ANXA1 in HUVECs, HDL still inhibited secretion of MCP-1 (34.8%, P<0.01), IL-8 (39.6%, P<0.05), VCAM-1(31%, P<0.01) and E-selectin (40.8%, P<0.05) by TNF-α.Therefore, Our findings demonstrated that ANXA1 mediated the anti-inflammatory function of HDL in TNF-α activated endothelial cells by inhibiting cell surface VCAM-1, ICAM-1 and anti-inflammatory mediator, was recently reported to play protective role in the progression of atherosclerosis, such as promoting plaque stability and counteracting arterial leukocyte recruitment [8,25]. This study identified that HDL could up-regulate ANXA1 in endothelial cells in vitro and in vivo, which raised a novel insight of its anti-inflammation in endothelial protection and further clarified the protective mechanism of ANXA1 in atherosclerosis.Based on previous studies, endothelial ANXA1 was impaired during endothelial dysfunction and vascular inflammation [6,7].…”
mentioning
confidence: 81%
“…7H-K, HDL inhibited secretion of MCP-1(33.8%, P<0.001), IL-8(37.1%, P<0.001), VCAM-1(37.7%, P<0.001) and E-selectin (41.8%, P<0.001) by TNF-α in HUVECs transfected by empty vector. After transfection of Ad-ANXA1 in HUVECs, HDL still inhibited secretion of MCP-1 (34.8%, P<0.01), IL-8 (39.6%, P<0.05), VCAM-1(31%, P<0.01) and E-selectin (40.8%, P<0.05) by TNF-α.Therefore, Our findings demonstrated that ANXA1 mediated the anti-inflammatory function of HDL in TNF-α activated endothelial cells by inhibiting cell surface VCAM-1, ICAM-1 and anti-inflammatory mediator, was recently reported to play protective role in the progression of atherosclerosis, such as promoting plaque stability and counteracting arterial leukocyte recruitment [8,25]. This study identified that HDL could up-regulate ANXA1 in endothelial cells in vitro and in vivo, which raised a novel insight of its anti-inflammation in endothelial protection and further clarified the protective mechanism of ANXA1 in atherosclerosis.Based on previous studies, endothelial ANXA1 was impaired during endothelial dysfunction and vascular inflammation [6,7].…”
mentioning
confidence: 81%
“…In a human proteomics study of coronary arteries, the levels of AnxA1 were found to be increased in atherosclerotic tissue compared with non-atherosclerotic tissue (Bagnato et al, 2007). Subsequently, two studies reported that the expression of AnxA1 was higher in carotid plaques from asymptomatic compared with plaques from symptomatic patients (Cheuk and Cheng, 2011;Viiri et al, 2013).…”
Section: Annexin A1 In Atherosclerosismentioning
confidence: 99%
“…Two studies of human carotid plaques suggested a plaque-stabilizing role for AnxA1 since the protein was more abundant in plaques from asymptomatic patients (Cheuk and Cheng, 2011;Viiri et al, 2013). Bagnato et al (Bagnato et al, 2007) reported increased AnxA1 levels in the atherosclerotic areas of human coronary arteries.…”
Section: Anxa1 Expression In Pbmcs In Relation To Glucocorticoid Sensmentioning
confidence: 99%
“…Such techniques include gel based methods like 2-DE, and non-gel based techniques like liquid chromatography tandem mass spectrometry (LC-MS/ MS) and capillary electrophoresis-mass spectrometry (CE-MS). Table 1 identifies different studies in which such techniques were applied in recent years [30,36,44,50,[52][53][54][55][56][57][58][59][60][61].…”
Section: Proteomicsmentioning
confidence: 99%